Supported small-size bimetallic oxide cluster and preparation method thereof

The preparation of loaded small-size bimetallic oxide clusters by calcined hydrotalcite precursors solves the problem of difficulty in preparing small-size nanoclusters in the prior art, and achieves high yield, stable structural and environmentally friendly catalyst preparation, which improves catalytic activity.

CN119500095APending Publication Date: 2025-02-25DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311020569.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-14
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

It is difficult to prepare loaded metal oxide nanoclusters with sizes less than 5 nanometers in the prior art, and traditional methods have problems with precious metal nanocluster aggregation and environmental pollution.

Method used

By calcining the hydrotalcite-like precursor {[MII1-xMIIIx(OH)2]x+[(An-)x/n·mH2O]}x-, a MIIMIIIOy bimetallic oxide cluster loaded at MIIO was prepared, achieving the load and structural stability of the small-sized bimetallic oxide cluster.

Benefits of technology

The high yield, stable structural and environmentally friendly preparation of small-sized bimetal oxide clusters is achieved, and the catalytic activity and reaction efficiency are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500095A_ABST
    Figure CN119500095A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nano materials, and particularly relates to a supported small-size bimetallic oxide cluster and a preparation method thereof. The load type small-size bimetallic oxide cluster comprises MIIO nano particles and MIIMIIIOy nano clusters, MII is any one of Cu, Mg, Zn, Co, Ni, Mn and Ca, MIII is any one of Fe, Al, Ga, In, Ce and Zr, y represents the number of oxygen, and the MIIMIIIOy nano clusters are loaded on the MIIO nano particles. The size of the MIIMIIIOy nano-cluster ranges from 2 nm to 4 nm. The synthesis method of the supported small-size bimetallic oxide cluster provided by the invention is simple and easy to implement, mild and controllable in condition and high in yield, and the MIIMIIIOy nano-cluster is supported on the MIIO nano-particles, is stable in structure and uniform in size, has rich oxygen vacancy defects and is beneficial to improvement of catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanomaterials, and particularly relates to a type of supported small-size bimetallic oxide clusters and a preparation method thereof. Background Art

[0002] Supported metal oxides are widely used in industrial catalytic reactions due to the strong metal-support interaction between the metal and the oxide support material and the significant catalytic activity they exhibit. Currently, in laboratories and industrial production, conventional methods for preparing supported metal oxides include physical mixing, impregnation, hydrothermal, precipitation, sol-gel, and ion exchange. Traditional methods can only prepare oxide solid solution particles larger than 5 nanometers, which are difficult to prepare due to the sharp increase in surface energy and a large number of surface defects of ~2-3 nanometer particles. Therefore, whether from the perspective of exploring scientific problems or from the perspective of practical industrial catalytic applications, it is very necessary to obtain small-sized metal oxides with controllable structures and uniform components using a simple, efficient, and low-cost catalyst preparation method.

[0003] For example, in an amine-functionalized mesoporous silica microsphere loaded with nanometal clusters (patent number: CN104741140A), Fe2O3, CuO, Fe 2-x Cu 1.5x O3 nano metal clusters, but the cluster size obtained in this patent is obviously greater than 4 nanometers. U.S. Patent (S.Mao, G.Mao, US 6686308B2) discloses a method for preparing high-load Pt / C and Pt-Ru / C catalysts, adding a carbon carrier to a "non-protected" Pt or Pt-Ru nano cluster colloid, adding an inorganic acid as a precipitation promoter, and depositing the Pt or Pt-Ru nano cluster on the carbon carrier. This catalytic preparation method easily causes the noble metal nano clusters to gather in the colloid or on the carrier surface. In addition, using a large amount of acid as a precipitant is also not conducive to environmental protection. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a method for preparing a type of supported small-sized bimetallic oxide clusters, by calcining a hydrotalcite precursor {[M II 1-x M III x (OH)2] x+ [ ( A n- ) x / n ·mH2O]} x- , thus obtaining the load at M II O'M II M III O yBimetallic oxide clusters have the characteristics of stable structure, uniform size, simple preparation method, mild conditions and high yield.

[0005] In order to achieve the above object, the technical solution of the present invention is as follows:

[0006] In one aspect, the present invention provides a type of supported small-sized bimetallic oxide clusters, wherein the supported small-sized bimetallic oxide clusters include M II O nanoparticles and M II M III O y Nanoclusters, where: M II is any one of Cu, Mg, Zn, Co, Ni, Mn, and Ca, M III is any one of Fe, Al, Ga, In, Ce, and Zr, y represents the number of oxygen; the M II M III O y Nanoclusters loaded on M II O nanoparticles; the M II M III O y The size of the nanoclusters is 2 to 4 nm.

[0007] Another aspect of the present invention provides a method for preparing the above-mentioned supported small-sized bimetallic oxide clusters, wherein the method comprises the following steps:

[0008] (1) M II Metal salt, M III The metal salt is dissolved in a solvent to obtain a precursor solution, and the precursor solution is added dropwise to an alkaline solution under stirring, and the pH of the reaction solution is adjusted to 8-14 until precipitation is complete, followed by heating at 30-90° C. for aging for 6-24 hours;

[0009] (2) separating the solid matter by centrifugation, washing, and drying to obtain a hydrotalcite-like precursor;

[0010] (3) Annealing the hydrotalcite precursor obtained in step (2) at 300-800° C. for 1-5 hours to obtain a supported small-sized bimetallic oxide cluster.

[0011] In the above technical solution, further, in the step (1), M II With M III The molar ratio is 1:1-10:1.

[0012] In the above technical solution, further, in the step (1), the alkaline solution is one or more of ammonia water, sodium carbonate, sodium bicarbonate, sodium hydroxide, and potassium hydroxide.

[0013] In the above technical solution, further, in the step (1), the stirring time is 2-40 minutes.

[0014] In the above technical solution, further, in the step (1), the solvent is one of methanol, ethanol, isopropanol and water.

[0015] In the above technical solution, further, in the step (2), the drying temperature is 60-120°C and the drying time is 8-24 hours.

[0016] In the above technical solution, further, in the step (3), the heating rate of the calcination is 5-20°C / min, and the gas atmosphere of the calcination is any one of nitrogen, argon and air.

[0017] The present invention uses a coprecipitation method to prepare a bimetallic hydrotalcite precursor, using the formula {[M II 1-x M III x (OH)2] x+ [ ( A n- ) x / n ·mH2O]} x- Indicates, where: x = 0.01-1, x and 1-x represent M II 、M III The molar percentage of A represents the anion added to the alkali solution, n represents the anion valence state of the metal salt, and m represents the number of water molecules. By calcining the hydrotalcite precursor, the supported bimetallic oxide nanoclusters, namely, M II M III O y Nanoclusters loaded on M II O nanoparticles.

[0018] The beneficial effects of the present invention are:

[0019] 1. The preparation method of a type of supported small-sized bimetallic oxide clusters provided by the present invention is simple and easy, with mild conditions, controllable and high yield.

[0020] 2. The supported small-sized bimetallic oxide clusters provided by the present invention are uniform in size compared to commonly used metal oxide nanoparticles.

[0021] 3. The supported small-sized bimetallic oxide clusters provided by the present invention have different valences of metal species and abundant oxygen vacancy defects. The high oxygen vacancy defects and the valences of different metal species promote the redox balance between the metal oxide catalytic reactions, which is beneficial to the improvement of catalytic activity. 4. The supported small-sized bimetallic oxide clusters provided by the present invention are prepared by calcining a hydrotalcite precursor {[M II1-x M III x (OH)2] x+ [ ( A n- ) x / n ·mH2O]} x- The obtained bimetallic oxide nanoclusters, M II M III O y Nanoclusters loaded on M II O nanoparticles, the bimetallic oxide hydrotalcite precursor has a large surface area, high metal dispersion and adjustable acid-base properties. Calcination causes the separation and reconstruction process of the precursor. Therefore, calcination of the hydrotalcite precursor can produce MIIMIIIOy nanoclusters supported by well-dispersed MIIO nanoparticles with stable structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 [Zn6Al2(OH) prepared in Example 1 16 ] Transmission electron microscopy (TEM) image of CO3·mH2O hydrotalcite precursor;

[0023] Figure 2 The Zn prepared in Example 1 0.75 Al 0.25 O 2.25 @Transmission electron microscopy (STEM) image of ZnO nanoclusters;

[0024] Figure 3 The Zn prepared in Example 1 0.75 Al 0.25 O 2.25 @Transmission electron microscopy (TEM) of ZnO nanoclusters;

[0025] Figure 4 The Zn prepared in Example 1 0.75 Al 0.25 O 2.25 @Photoelectron spectrum of ZnO nanoclusters (O1sXPS);

[0026] Figure 5 Mn prepared in Example 2 0.75 Fe 0.25 O 2.25 @Transmission electron microscopy (TEM) image of MnO nanoclusters;

[0027] Figure 6 Co prepared in Example 3 0.5 Ce 0.25 O 1.75 @Transmission electron microscopy (TEM) image of CoO nanoclusters;

[0028] Figure 7 The Ca prepared in Example 4 0.8 Zr 0.2 O 2.25 @ Transmission electron microscopy (TEM) of CaO nanoclusters;

[0029] Figure 8 Zn prepared in Comparative Example 1 30 AlO x @Transmission electron microscopy (TEM) of ZnO nanoclusters;

[0030] Fig. 9 Transmission electron microscopy (TEM) image of ZnO prepared in Comparative Example 2;

[0031] Fig.10 This is the transmission electron microscopy (TEM) image of Al2O3 prepared in Comparative Example 3. DETAILED DESCRIPTION

[0032] The following examples may enable those skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0033] Unless otherwise specified, the materials used in the embodiments of the present invention can be obtained through commercial channels or prepared according to conventional methods well known to those skilled in the art.

[0034] Example 1

[0035] (1) 0.142 g of Zn(NO3)2 and 0.053 g of Al(NO3)3 were dissolved in 10 ml of deionized water, and the precursor solution was added dropwise to 10 ml of an alkaline solution containing 0.64 g of NaOH and 0.53 g of Na2CO3 under stirring. The mixture was stirred vigorously for 5 minutes, and then the solution was kept without stirring and aged in an oven at 70°C overnight (>12 hours);

[0036] (2) The solid matter was separated by centrifugation, then washed with deionized water, and finally dried at 120°C for 10 hours to obtain a hydrotalcite precursor [Zn6Al2(OH) 16 ]CO3·mH2O;

[0037] (3) The hydrotalcite precursor obtained in step (2) was heated from 120°C to 450°C in a synthetic air atmosphere at a heating rate of 10°C / min for 2 hours, and then cooled naturally after calcination to obtain Zn 0.75 Al 0.25 O 2.25 @ZnO nanoclusters.

[0038] Example 1 By calcining [Zn6Al2(OH) 16]CO3·mH2O hydrotalcite precursor (such as Figure 1 Zn 0.75 Al 0.25 O 2.25 @ZnO nanoclusters, HAADF-STEM and TEM characterization results show that Zn 0.75 Al 0.25 O 2.25 @ZnO nanoclusters are composed of 2-4 nm small ZnAlOx clusters anchored on ZnO nanoparticles (e.g. Figure 2 , 3 As shown), the XPS O1s spectrum characterization results show that (as shown Figure 4 Shown) Zn 0.75 Al 0.25 O 2.25 @ZnO nanoclusters have a large amount of surface lattice oxygen (O L ), oxygen vacancies (O V ), a large number of surface defects are attributed to Zn 0.75 Al 0.25 O 2.25 Small ZnAlOx clusters with a size of 2.0-3.6 nm in @ZnO are beneficial to improve the catalytic activity.

[0039] Example 2

[0040] (1) 0.134 g of Mn(NO3)2 and 0.06 g of Fe(NO3)3 were dissolved in 10 ml of deionized water, and the precursor solution was added dropwise to 10 ml of an alkaline solution containing 0.64 g of NaOH and 0.53 g of Na2CO3 under stirring. After vigorous stirring for 5 minutes, the solution was kept without stirring and aged in an oven at 70°C overnight (>12 hours);

[0041] (2) The solid matter was separated by centrifugation, then washed with deionized water, and finally dried at 120°C for 10 hours to obtain a hydrotalcite precursor [Mn6Fe2(OH) 16 ]CO3·nH2O;

[0042] (3) The hydrotalcite precursor obtained in step (2) was heated from 120°C to 450°C in a synthetic air atmosphere at a heating rate of 10°C / min for 2 hours, and then cooled naturally after calcination to obtain Mn 0.75 Fe 0.25 O 2.25 @MnO nanoclusters.

[0043] Example 2 By calcining [Mn6Fe2(OH) 16 ]CO3·nH2O hydrotalcite precursor prepared Mn 0.75 Fe 0.25 O2.25 @MnO nanoclusters, TEM characterization results show that Mn 0.75 Fe 0.25 O 2.25 @MnO nanoclusters are composed of 2-4 nm small MnFeOx clusters anchored on MnO nanoparticles (such as Figure 5 shown).

[0044] Example 3

[0045] (1) 0.089 g of (CH3COO)2Co and 0.082 g of Ce(NO3)3 were dissolved in 10 ml of deionized water. The precursor solution was added dropwise to 10 ml of an alkaline solution containing 1.12 g of KOH under stirring. After vigorous stirring for 5 minutes, the solution was kept without stirring and aged in an oven at 70°C overnight (>12 hours);

[0046] (2) The solid matter was separated by centrifugation, then washed with deionized water, and finally dried at 120°C for 10 hours to obtain Co4Ce2(OH) 14 nH2O hydrotalcite precursor;

[0047] (3) The hydrotalcite precursor obtained in step (2) was calcined in a synthetic air atmosphere at a heating rate of 10°C / min from 120°C to 450°C for 2 hours, and then cooled naturally after calcination to obtain Co 0.5 Ce 0.25 O 1.75 @CoO nanoclusters.

[0048] Example 4

[0049] (1) 0.131 g of Ca(NO3)2 and 0.02 g of Zr(NO3)3 were dissolved in 10 ml of deionized water, and the precursor solution was added dropwise to 10 ml of an alkaline solution containing 0.64 g of NaOH and 0.53 g of Na2CO3 under stirring. The mixture was stirred vigorously for 5 minutes, and then the solution was kept without stirring and aged in an oven at 70°C overnight (>12 hours);

[0050] (2) The solid matter was separated by centrifugation, then washed with deionized water, and finally dried at 120° C. for 10 hours to obtain a hydrotalcite precursor [Ca8Zr2(OH) 20 ]CO3.nH 2 O, and obtain the hydrotalcite precursor [Ca8Zr2(OH) 20 ]CO3·nH2O;

[0051] (3) calcining the hydrotalcite precursor obtained in step (2) in a synthetic air atmosphere at a heating rate of 10°C / min from 120°C to 450°C for 2 hours, and then cooling naturally after calcination to obtain Ca 0.8 Zr 0.2 O 2.25 @CaO nanoclusters.

[0052] Comparative Example 1

[0053] (1) 0.567 g of Zn(NO3)2 and 0.02 g of Al(NO3)3 were dissolved in 15 ml of deionized water, and the precursor solution was added dropwise to 20 ml of an alkaline solution containing 1.2 g of NaOH and 1.06 g of Na2CO3 under stirring. The mixture was stirred vigorously for 5 minutes, and then the solution was kept without stirring and aged in an oven at 70°C overnight (>12 hours);

[0054] (2) The solid matter was separated by centrifugation and then washed with deionized water. 30 Al(OH) 61 ]CO3·nH2O hydrotalcite precursor was dried at 120°C for 10 hours to obtain a hydrotalcite precursor [Zn 30 Al(OH) 61 ]CO3·nH2O;

[0055] (3) The hydrotalcite precursor obtained in step (2) was heated from 120°C to 450°C in a synthetic air atmosphere at a heating rate of 10°C / min for 2 hours, and then cooled naturally after calcination to obtain Zn 30 AlO x @ZnO nanoclusters.

[0056] Figure 8 Zn prepared in Comparative Example 1 30 AlO x @TEM image of ZnO. It can be seen from the image that the bimetallic oxide basically only has zinc oxide nanoparticles with a size of ~50 nanometers, which increases in size.

[0057] Fig. 9 Transmission electron microscopy (TEM) image of ZnO prepared in Comparative Example 2;

[0058] Fig.10 This is the transmission electron microscopy (TEM) image of Al2O3 prepared in Comparative Example 3.

[0059] Comparative Example 2

[0060] (1) 0.142 g of Zn(NO3)2 was dissolved in 10 ml of deionized water. The precursor solution was added dropwise to 10 ml of an alkaline solution containing 0.64 g of NaOH and 0.53 g of Na2CO3 under stirring. The mixture was stirred vigorously for 5 minutes. The solution was kept without stirring and aged in an oven at 70°C overnight (>12 hours).

[0061] (2) separating the solid matter by centrifugation, then washing with deionized water, and finally drying at 120° C. for 10 hours;

[0062] (3) The obtained in step (2) is calcined in a synthetic air atmosphere at a heating rate of 10°C / min from 120°C to 450°C for 2 hours, and then cooled naturally after calcination to obtain ZnO.

[0063] Fig. 9 This is a TEM image of ZnO prepared in Comparative Example 2. It can be seen from the image that after calcination, the zinc oxide nanoparticles agglomerated and enlarged to form a block structure with a size of 50-100 nanometers.

[0064] Comparative Example 3

[0065] (1) 0.053 g of Al(NO3)3 was dissolved in 10 ml of deionized water. The precursor solution was added dropwise to 10 ml of an alkaline solution containing 0.64 g of NaOH and 0.53 g of Na2CO3 under stirring. The mixture was stirred vigorously for 5 minutes. The solution was kept without stirring and aged in an oven at 70°C overnight (>12 hours).

[0066] (2) separating the solid matter by centrifugation, then washing with deionized water, and finally drying the precursor at 120° C. for 10 hours;

[0067] (3) The product obtained in step (2) is calcined in a synthetic air atmosphere at a heating rate of 10°C / min from 120°C to 450°C for 2 hours, and then cooled naturally after calcination to obtain Al2O3.

[0068] Fig.10 The TEM of Al2O3 prepared in Comparative Example 3 shows that bulk Al2O3 is obtained with larger size.

[0069] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation methods. The protection scope of the present invention shall be subject to the scope defined in the claims. Other different forms of changes or modifications may be made based on the above description. Obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A type of supported small-sized bimetallic oxide cluster, characterized in that: The supported small-sized bimetallic oxide clusters include M II O nanoparticles and M II M III O y Nanoclusters, where: M II is any one of Cu, Mg, Zn, Co, Ni, Mn, and Ca, M III is any one of Fe, Al, Ga, In, Ce, and Zr, y represents the number of oxygen atoms, and the M II M III O y Nanoclusters loaded on M II O nanoparticles; the M II M III O y The size of the nanoclusters is 2-4 nm.

2. A method for preparing the supported small-sized bimetallic oxide clusters according to claim 1, characterized in that: The method comprises the following steps: (1) M II Metal salt, M III The metal salt is dissolved in a solvent to obtain a precursor solution, and the precursor solution is added dropwise to an alkaline solution under stirring, and the pH of the reaction solution is adjusted to 8-14 until precipitation is complete, followed by heating at 30-90° C. for aging for 6-24 hours; (2) separating the solid matter by centrifugation, washing, and drying to obtain a hydrotalcite-like precursor; (3) Annealing the hydrotalcite precursor obtained in step (2) at 300-800° C. for 1-5 hours to obtain a supported small-sized bimetallic oxide cluster.

3. The preparation method according to claim 2, characterized in that: In the step (1), M II With M III The molar ratio is 1:1-10:

1.

4. The preparation method according to claim 2, characterized in that: In the step (1), the alkaline solution is one or more of ammonia water, sodium carbonate, sodium bicarbonate, sodium hydroxide, and potassium hydroxide.

5. The preparation method according to claim 2, characterized in that: In the step (1), the stirring time is 2-40 minutes.

6. The preparation method according to claim 2, characterized in that: In the step (1), the solvent is one of methanol, ethanol, isopropanol and water.

7. The preparation method according to claim 2, characterized in that: In the step (2), the drying temperature is 60-120° C. and the drying time is 8-24 hours.

8. The preparation method according to claim 2, characterized in that: In the step (3), the heating rate of the annealing is 5-20°C / min, and the annealing gas atmosphere is any one of nitrogen, argon and air.

Citation Information

Patent Citations

  • Amino functionalized mesoporous silica micro-sphere loaded type heterogeneous catalyst as well as preparation method and application thereof

    CN104741140A

  • Supported nanoparticle catalyst

    US6686308B2